The Role of Human Epididymis Protein 4 in the Diagnosis and Prognosis of Diseases: An Umbrella Review of Systematic Reviews and Meta-Analyses of Observational Studies - Sun, Ming-Li; Yang, Zhi-Yong; Wu, Qi-Jun; Li, Yi-Zi; Li, Xin-Yu; Liu, Fang-Hua; Wei, Yi-Fan; Wen, Zhao-Yan; Lin, Bei; Gong, Ting-Ting (Frontiers in Medicine, 2022)
Background: The application of human epididymis protein 4(HE4) in diverse health diseases, especially in cancers, has been extensively studied in recent decades. To summarize the existing evidence of the aforementioned topic, we conducted an umbrella review to systematically evaluate the reliability and strength of evidence regarding the role of HE4 in the diagnostic and prognostic estimate of diverse diseases. Methods: Electronic searches in PubMed, Web of Science, and Embase were conducted from inception to September 16, 2021 for meta-analyses, which focus on the role of HE4 in the diagnosis and prognosis of diseases. This study protocol has been registered at PROSPERO(CRD42021284737). We collected the meta-analysis effect size of sensitivity, specificity, positive predictive value, and negative predictive value from diagnostic studies and gathered the HR of disease-free survival, overall survival, and progression-free survival from prognostic studies. For each sys-tematic review and meta-analysis, we used a measurable tool for evaluating systematic reviews and meta-analysis(AMSTAR)to evaluate the methodological quality. Additionally, we assessed the quality of evidence on estimating the ability of HE4 in the diagnosis and prognosis of diverse diseases by the Grading of Recommendations Assess-ment, Development and Evaluation (GRADE) guideline. Results: Overall, 20 meta-analyses including a total of 331 primary studies of different diseases were examined, mainly including ovarian cancer(n=9), endometrial cancer(n=6), and lung cancer(n=4). The methodological quali-ties of all studies were rated as moderate(45%) or high(55%) by the AMSTAR. According to the GRADE, the cer-tainties of 18 diagnostic evidences (9 for sensitivity, 9 for specificity) were rated as moderate(34%), low(33%), and very low(33%). Moreover, outcomes from prognosis studies showed one evidence (1 for disease-free survival) with high certainty in regard to cancers (including endometrial cancer, ovarian cancer, and lung cancer) with the remaining three being moderate. Conclusions: This umbrella review suggested that HE4 was a favor biomarker in the prognosis of cancers, which was supported by high certainty of evidence. Additionally, HE4 could provide a suitable method for the diagnosis of endometrial cancer, ovarian cancer, and lung cancer with moderate certainty evidence. Further large prospective cohort studies are needed to better elucidate the diagnostic and prognostic role of HE4 in diseases.